Вплив когнітивних викривлень на розвиток економіки - Мамчин, М. М.; Яричевська, Я. І.; Mamchyn, M. M.; Yarychevska, Y. I. (Видавництво Львівської політехніки, 2023)
Досліджено когнітивні викривлення (ілюзії) та можливості використання впливу когнітивних та емоційних чинників на прийняття рішень різними суб’єктами ринку в умовах невизначеності. Висвітлено теоретичні засади ірраціональної поведінки економічних суб’єктів із урахуванням когнітивних або соціальних причин. Досліджено дві системи мислення. Виявлено чинники, що впливають на поведінку індивідуумів, та причини когнітивних викривлень, які можна враховувати під час формування економічних стимулів і навіть економічних процесів загалом. Окреслено вплив найвідоміших когнітивних ілюзій на різні види економічних суб’єктів. Правильна діагностика когнітивних викривлень у поведінці економічних суб’єктів у бізнесі надалі дасть змогу за допомогою належних впливів трансформувати її у потрібний стан.

The article studies cognitive distortions (illusions) and the possibilities of using cognitive and emotional factors to make decisions by different market actors in conditions of uncertainty. The theoretical foundations of the irrational behavior of economic actors, based on cognitive or social reasons, are highlighted. The authors note that the functioning of the cognitive sphere of a person is often accompanied by certain errors that are scientifically attributed to cognitive distortions in the rational behavioral paradigm that cause distortions in the perception of reality. Based on the understanding that the behavior of the human brain is sufficiently rational, since its work aims to save resources, resulting in logical errors, in other words, cognitive distortions that are caused by limited cognitive resources, as well as external limiting factors or insufficient motivation. Therefore, it can be considered that since the brain uses cognitive illusions to save resources to accelerate decision making, said process has evolved evolutionarily in order to survive. It has been established that the inability of the human brain to fully process the entire huge body of information when making decisions and leads to the existence of cognitive distortions, which in turn can negatively affect not only the geopolitical situation in the world, but also cause the death of many other people, so it is necessary to thoroughly investigate their influence on the behavior of economic actors. The article explores two systems of thinking. In the I system, thinking is distinguished by the intuitiveness of the decisions made, the high speed of thought processes with their minimal awareness. In the II system, thinking is characterized by controllability, systematicity, rationality, that is, it is logically justified and conscious. Based on the characteristics of each of the systems, it is possible to understand how individuals make decisions and what were the subconscious reasons for a particular reaction. Factors affecting the behavior of individuals and the causes of cognitive distortions that can be taken into account when building economic incentives and even economic processes in general have been identified. The influence of the most faithful cognitive illusions on different types of economic entities is outlined. Proper diagnosis of cognitive distortions in the behavior of economic entities in business in the future will allow, with the help of proper influences, to transform it into the desired state.
The impact of cognitive distortions on economic development
Keywords: когнітивні викривлення; невизначеність; ірраціональна поведінка; економічні суб’єкти; прийняття рішень; економіка; cognitive distortions; uncertainty; irrational behavior; economic subjects; decision making; economy; 338.658